2015
DOI: 10.1016/j.ijgo.2015.06.049
|View full text |Cite
|
Sign up to set email alerts
|

High‐risk human papillomavirus infection in the prediction of poor treatment response and disease recurrence in patients with vulvovaginal condyloma

Abstract: A high HR-HPV load is a risk factor for recurrence, but is not related to treatment response. A poor treatment response is more related to abnormal cytology than it is to viral load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Nonetheless, scant data exist when testing for HR-HPV types restricted to cervico-vaginal smears of patients with AGWs. A study from South Korea on 18 patients reported that 50% of cervical scrapings were infected with HR-HPV types (18), while a slightly higher rate was found by researchers in Ireland (16). Although, our rate of 34.2% is considerably lower compared to the aforementioned studies, it is strikingly similar to what was reported (33%) in an older study from Greece which included 100 patients with AGWs (17).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Nonetheless, scant data exist when testing for HR-HPV types restricted to cervico-vaginal smears of patients with AGWs. A study from South Korea on 18 patients reported that 50% of cervical scrapings were infected with HR-HPV types (18), while a slightly higher rate was found by researchers in Ireland (16). Although, our rate of 34.2% is considerably lower compared to the aforementioned studies, it is strikingly similar to what was reported (33%) in an older study from Greece which included 100 patients with AGWs (17).…”
Section: Discussionmentioning
confidence: 87%
“…It is noteworthy that patients with recurrent AGWs were diagnosed with cervico-vaginal HR-HPV types more commonly, as opposed to those with a single episode of AGWs. Recurrent AGWs have already been associated with high HR-HPV DNA load both in cervical scrapings (18) and in AGWs tissue samples (9) in smaller studies. In line with these, our finding may indicate that HR-HPV types could trigger AGWs recurrences more often.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation